Рroblems of activity of enterprises in the hospitality industry in modern conditions - Nikitina, Tatyana (My University, 2023)
Domestic enterprises in the hospitality industry have suffered heavy losses due to the COVID-19 pandemic, full-scale war and martial law in the country. The full-scale war affected the reduction of occupancy in hotels. Researching the current state of hospitality industry enterprises and determining the ways of their preservation, existence and development in the modern conditions of martial law in the country is relevant. Вітчизняні підприємства індустрії гостинності зазнали великих втрат внаслідок пандемії COVID-19, повномасштабної війни та військового стану в країні. Повномасштабна війна вплинула на скорочення завантаженості номерного фонду в готелях. Актуальним є дослідження сучасного стану підприємств індустрії гостинності та визначення шляхів їх збереження, існування та розвитку в сучасних умовах воєнного стану в країні.
Keywords: кафедра готельно-ресторанної справи; hotel business; modern state of hospitality industry enterprises; готельний бізнес; сучасний стан підприємств індустрії гостинності